Enhancing the all sports booking system: addressing inefficiencies and proposed improvements for user satisfaction - Mohd Zahibi, Muhammad Faris Hami; Hamidon, Huda; Azmi, Nik Mohammad Wafiy; Mohamad Arifin, Mohamad Syauqi; Abu Bakar, Normashidayu (Faculty of Information Management, 2025)
The utilization of digital systems to enhance business operations is a well-established strategy among enterprises today. Many businesses choose to adopt technology to remain competitive, however, it is important to note that not all system implementations will achieve complete success without encountering issues. This study examines challenges that the All Sports Booking System needs to address, which relate precisely to system inefficiencies, user dissatisfaction, and trust issues. The study identified some major issues: double booking, slow response time, and poorly designed user interface. The objective is to propose certain improvements in the system based on the user’s feedback. Data collected using interviews and surveys. Findings revealed usability and reliability of the systems are the main problems that affected users' trust in using the system. Recommendations for future enhancement include real-time update issues, interface usability, and system security and transparency.